2020
DOI: 10.1016/j.btre.2019.e00407
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of carotenoids production by Rhodotorula mucilaginosa (MTCC-1403) using agro-industrial waste in bioreactor: A statistical approach

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 25 publications
2
55
0
Order By: Relevance
“…However, they are similar to the carotenoids-specific production obtained by optimization of Rh. mucilaginosa growth in diverse agro-industrial wastes (Sharma and Ghoshal 2020). At AW and 30% AE, although Rh.…”
Section: Carotenoid Production By Rh Mucilaginosamentioning
confidence: 97%
See 1 more Smart Citation
“…However, they are similar to the carotenoids-specific production obtained by optimization of Rh. mucilaginosa growth in diverse agro-industrial wastes (Sharma and Ghoshal 2020). At AW and 30% AE, although Rh.…”
Section: Carotenoid Production By Rh Mucilaginosamentioning
confidence: 97%
“…Several studies have demonstrated the feasibility of producing carotenoids from low-cost substrates (Kaur et al 2019;Sharma and Ghoshal 2020;Urnau et al 2019). In this work, we explore the production of carotenoids, in particular, torulene and torularhodin, by a strain of Rhodotorula mucilaginosa using different medium derived from alperujo as cheap substrates.…”
Section: Introductionmentioning
confidence: 99%
“…trispora mold [ 28 ]. Efficient producers of microbial β-carotene also include the yeast Rhodotorula glutinis [ 6 , 29 ], Rhodotorula mucilaginosa [ 30 ], and Sporidiobolus pararoseus [ 31 , 32 ].…”
Section: Characteristics Of Some Fungal Carotenoidsmentioning
confidence: 99%
“…In addition, industrial wastewaters are successfully used for production of phycocyanins and carotenoid pigments by microalgae (Singh et al, 2019;Arashiro et al, 2020). Intracellular carotenoids (β-carotene, γ-carotene, torulene, and torularhodin) from Rhodotorula species have been produced by using different agro-industrial byproducts as sugarcane bagasse, wheat bran, rice bran, silage, whey, raw glycerol, corn steep liquor, sugarcane molasses, waste chicken feathers, fruit waste extract, and many others (Sharma and Ghoshal, 2019;Korumilli et al, 2020). These pigments could have applications in food and feed as well as in health, pharmaceutical products and cosmetics, generating a market value expected to reach over $2.0 billion by 2022 (Elfeky et al, 2019;Tang et al, 2019).…”
Section: Microbial Pigment Production Using Agro-industrial Byproductsmentioning
confidence: 99%